2014
DOI: 10.4161/hv.29857
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell defects in the colorectal cancer

Abstract: Colorectal cancer (CRC) results from the accumulation of both genetic and epigenetic alterations of the genome. However, also the formation of an inflammatory milieu plays a pivotal role in tumor development and progression. Dendritic cells (DCs) play a relevant role in tumor by exerting differential pro-tumorigenic and anti-tumorigenic functions, depending on the local milieu. Quantitative and functional impairments of DCs have been widely observed in several types of cancer, including CRC, representing a tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 154 publications
(282 reference statements)
2
74
0
Order By: Relevance
“…DCs, critical regulators of host immunity, serve as a bridge between the innate and adaptive immune responses. DCs also play a relevant role in tumorigenesis by exerting differential pro-tumorigenic and antitumorigenic functions, depending on the local microenvironment (Legitimo et al, 2014). In TME, the APC function of DCs is suppressed by soluble factors secreted from tumor cells and tumor-associated cells.…”
Section: Discussionmentioning
confidence: 99%
“…DCs, critical regulators of host immunity, serve as a bridge between the innate and adaptive immune responses. DCs also play a relevant role in tumorigenesis by exerting differential pro-tumorigenic and antitumorigenic functions, depending on the local microenvironment (Legitimo et al, 2014). In TME, the APC function of DCs is suppressed by soluble factors secreted from tumor cells and tumor-associated cells.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system plays an important role in the protection of the host against tumour onset (i.e., tumour immunosurveillance) [10]. In addition to tumour cells, stromal and immune cells are also present in the tumour microenvironment, where tumour cells often either recruit or locally induce their proliferation or differentiation to release an array of cytokines that participate in the immune response [10][11][12]. In colon cancer, T and B lymphocytes have been found in proximal colon tumour tissue [5], and natural killer (NK) cells, monocytes/macrophages, dendritic cells (DCs), mast cells, and Tables 1 and 2 show the clinical characteristics of the patients included in this study.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Impairment of DC differentiation was often found to be associated with a poor prognosis of cancer as well as resistance to therapies. 8 In addition, Lim DS et al found that expression of TGF-b in renal adenocarcinoma reduced the efficacy of DCbased immunotherapy in mice model. 9 Furthermore, the study by Dumitriu IE et al showed that lung carcinoma cell-culture supernatant treated DCs reduced expression of CD86 and production of IL-12 and TNF-a.…”
Section: Introductionmentioning
confidence: 99%